The Material and Energy Conversion Potential from Municipal Waste in Padang City: Business Chance and Future Prospective - Putra, Alqadri Asri; Rasyidin, Azwar (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2024)
Padang City, the capital city of West Sumatra Province, is expected to grow and reach a population of 1 million by 2035. However, this growth also means an increase in municipal solid waste, projected to be about 256,000 tons annually. At the same time, there is potential for waste-to-energy conversion in Padang City due to the demand for renewable energy and business opportunities. This study is based on existing literature and data, which were analyzed using a statistical approach and municipal solid waste management calculations. The study conducted scenarios that show potential energy conversions. The first scenario involves converting solid waste to gas and using it directly as biogas. The second scenario involves converting biogas from solid waste to electricity and distributing it for household use. The last scenario consists of using small and medium-sized biodigesters to convert gas into electricity, which will then be used as a charging station for electric vehicles (EVs). The first scenario can generate the most significant profit, while the third scenario suits small and medium businesses. However, each scenario has its pros and cons. Still, it's crucial to consider regulation issues, government support, and public awareness of the environmental problems to implement these waste-to-energy conversion practices on-site successfully.